The study of the relationship between thermal conductivity and porosity, permeability, humidity of sedimentary rocks of the West Siberian Plate - Duchkov Albert D.; Ayunov Dmitry E.; Rodyakin Sergey V.; Yan Petr A. (Общество с ограниченной ответственностью «Георесурсы», 2018)
The determination of correlation between thermal conductivity and structural parameters (porosity, permeability, humidity) of sedimentary rocks is a very urgent task. This article analyzes and compares the results of measurements of these parameters for ~300 samples of Mesozoic sandstones and siltstones from the core of 18 wells drilled in the north-eastern and southern regions of the West Siberian plate. The thermal conductivity of all samples was measured in the dry state and some (90 samples) – after saturation with water. Porosity and permeability are determined for 280 and 230 samples, respectively. The obtained data are used to establish linear correlation connections between thermal conductivity, porosity and permeability. The most interesting are rather stable dependences of thermal conductivity of dry and water-saturated samples between themselves and with porosity. The established correlation dependences are interesting in practical terms. Some of them can be used to approximate the thermal conductivity of watersaturated rocks by measurements of dry rocks or even only by the porosity value. The relationship between the thermal conductivity of sedimentary rocks and porosity can be used for rapid assessment of porosity of rocks on advanced measurements of thermal conductivity of a full-size core. It is obvious that the revealed correlation connections require further clarification.
Keywords: West Siberian plate; Mesozoic sandstones and siltstones; thermal conductivity; porosity; permeability; humidity; correlation dependence; Mesozoic; Мезозой